2014
DOI: 10.1259/bjr.20140299
|View full text |Cite
|
Sign up to set email alerts
|

The utility of atlas-assisted segmentation in the male pelvis is dependent on the interobserver agreement of the structures segmented

Abstract: Objective: To investigate the relationship between the ability of atlas-based autosegmentation to reduce outlining time in the male pelvis (body, bladder, rectum, femoral heads, prostate and seminal vesicles) and the interobserver agreement in the delineation of these structures. To examine any increase of the interobserver agreement with the use of an autosegmentation tool. Methods: We created atlases in the ABAS™ system v. 2.0 (Elekta, Crawley, UK) and recorded the time to delineate the above structures on e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
27
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(28 citation statements)
references
References 20 publications
1
27
0
Order By: Relevance
“…The DL-based AST evaluated in this study could provide a basis for improving the accuracy and consistency of the most critical step in radiation delivery to control disease and limit adverse effects related to errors in the delineation of structures in RTP of prostate cancer patients. Langmack et al found that the DSC should be larger than 0.65 to save time using AST and time saving increases linearly with the DSC [27]. The mean DSC per patient in all clinics was higher than 0.60 and only in two scans below 0.65, indicating there should have been reasonable time saved in all clinics.…”
Section: Discussionmentioning
confidence: 95%
“…The DL-based AST evaluated in this study could provide a basis for improving the accuracy and consistency of the most critical step in radiation delivery to control disease and limit adverse effects related to errors in the delineation of structures in RTP of prostate cancer patients. Langmack et al found that the DSC should be larger than 0.65 to save time using AST and time saving increases linearly with the DSC [27]. The mean DSC per patient in all clinics was higher than 0.60 and only in two scans below 0.65, indicating there should have been reasonable time saved in all clinics.…”
Section: Discussionmentioning
confidence: 95%
“…The total segmentation time including the manual operator interaction time was less than 1.5 min per 3D image which is substantially less than fully manual delineation time of 4.46 min reported in Ref. .…”
Section: Discussionmentioning
confidence: 65%
“…PCa radiation therapy planning is performed with the prostate border delineated on computed tomography (CT) images . However, due to the low soft tissue contrast between the prostate and surrounding tissues, manual contouring of the prostate in CT images is time consuming and is subject to high intraobserver and interobserver variability . Therefore, computer‐assisted segmentation algorithms are being investigated and developed to perform prostate contouring more quickly and more reproducibly compared to manual segmentation.…”
Section: Introductionmentioning
confidence: 99%
“…The results are comparable to the previously published work in the literature with a higher average sensitivity rate. The average 3D segmentation time, including the manual operator interaction time, is 75 seconds per image which is more than three times lower than manual prostate segmentation time reported in [21]. Since the presented technique is not related to previously acquired, and/or segmented CT images from the same target patient, it could be used for radiation therapy planning CT image segmentation.…”
Section: Discussionmentioning
confidence: 86%